Anatomy of the root of eight species of emergent aquatic macrophytes from the upper Paraná river, Paraná State, Brazil floodplain - doi: 10.4025/actascibiolsci.v32i3.5509 (Acta Scientiarum. Biological Sciences, 2010)
The upper Paraná River floodplain is characterized by the existence of several aquatic and transitional habitats between the aquatic and terrestrial environment, influencing the presence and distribution of aquatic macrophytes. Samples were taken from different places and permanent slides were prepared for analysis and capture of images with the objective of comparing the anatomy of the roots of eight species of emergent aquatic macrophytes. The species feature uniseriate epidermis with narrow and long cells, cortex composed of uniseriate or biseriate exodermis, with or without thickening, aerenchyma with great gaps, uniseriate endodermis, with or without thickening, continuous or interrupted pericycle, and central cylinder with variable number of xylem poles.